Pembelajaran Pendidikan Agama Kristen Bagi Siswa Tunarungu di Era New Normal - Nova Lisye Sinaulan; Ellen S. Kambey; Semuel Selanno (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to describe and analyze in depth Christian Religious Education Learning for Deaf Students In The New Nomal Era. Deaf children are children who experience obstacles in their hearing either overall or still have residual hearing. This study uses a qualitative method with a case study approach. Data was collected through observation, interviews, and documentation studies. The data analysis technique used begins with analyzing the data before going into the field, after that analyzing the data in the field with the stages: (1) condensing data by recording, recording data, (2) presenting data with descriptive descriptions and narrative texts, (3) concluding data by processing the data obtained and drawing conclusions. The results showed that PAK learning in the new normal era was carried out online and offline, using MTPJ as teaching material, using the lecture method and the repeat method. Factors that support learning: there is a patient attitude and good cooperation from teachers and parents in educating deaf students. Constraint factors include: there are no educators with PAK backgrounds, there is no PAK curriculum and learning tools.